Multiple Hydatid Cysts in Lungs, Liver and Spleen - Matar, Ayad J.; Hadbool, Saad M. (AL-Kindy College Medical Journal, 2013)
We presented here a 25years old lady with a multiple hatdtid cysts in lung and liver and spleen in large number in each organ. Which regarded inoperable and difficult to treared.We use medical treatment with antihelimenthes drugs in new regime and follow-up over 1year clinically, laboratory investigations, U/s and CT.scan. There was good disappearance of liver and spleen cysts with very good response in lungs.